2009
DOI: 10.1186/1472-698x-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Something old or something new? Social health insurance in Ghana

Abstract: BackgroundThere is considerable interest at present in exploring the potential of social health insurance to increase access to and affordability of health care in Africa. A number of countries are currently experimenting with different approaches. Ghana's National Health Insurance Scheme (NHIS) was passed into law in 2003 but fully implemented from late 2005. It has already reached impressive coverage levels. This article aims to provide a preliminary assessment of the NHIS to date. This can inform the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
235
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(247 citation statements)
references
References 9 publications
7
235
0
5
Order By: Relevance
“…The consequence is increased cost resulting from increasing utilisation paid for from the mostly tax-based financing sources, which seems to grow more slowly than enrolment and consequent use. 13 Problems of fraud and corruption were argued to be particularly evident in the early stages of implementation of the Scheme (in the form of what participants described as client/provider shopping) with some indication from interviewees that there has been improvement in more recent years. The study acknowledges that fraud is a challenge for insurance systems the world over.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consequence is increased cost resulting from increasing utilisation paid for from the mostly tax-based financing sources, which seems to grow more slowly than enrolment and consequent use. 13 Problems of fraud and corruption were argued to be particularly evident in the early stages of implementation of the Scheme (in the form of what participants described as client/provider shopping) with some indication from interviewees that there has been improvement in more recent years. The study acknowledges that fraud is a challenge for insurance systems the world over.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the main goal of the NHIS is to make healthcare affordable to all by removing OOP payment at the point of service, and to achieve equity of access based on need, rather than ability to pay. 1,12,13 The scheme is financed from several sources including earmarked tax (2.5% value added tax -hereafter referred to as VAT), 2.5% of the 17.5% of formal sector employees' contribution to Social Security and National Insurance Trust (SSNIT), budgetary allocation, donations, investments, grants and annual contributions from informal sector employees and formal sector employees who do not contribute to SSNIT. Membership is open to all residents of Ghana upon subscription to the scheme (exception being Ghana armed forces and police service, and those with proof of holding a private health insurance scheme).…”
Section: Summary Of the Main Elements Of Ghana's National Health Insumentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 Because of the immense benefits inherent in prepayment health-care financing methods, quite a number of African countries have embraced it, and this have been proven as an effective means of achieving universal health coverage. 34,36 As part of the efforts to achieve universal coverage, the NHIS in Nigeria was established, which commenced operations some years ago. However, this study showed that a negligible few of the respondents were aware about and also reported paying for health care through the scheme.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, Ghana and Chile increased the VAT rate and specifically earmarked the additional VAT percentages to fund their health insurance programs (Witter and Garshong, 2009). Zimbabwe has since 1999 imposed an additional 3% tax on the income of formal sector employees as a national AIDS levy raising $26 million in additional revenue in 2011, enabling 70,000 Zimbabweans to access antiretroviral therapy (UNAIDS, 2012).…”
Section: Earmarking Taxes For Healthmentioning
confidence: 99%